(untitled) (CIPEEX, 2025)
Anterior cruciate ligament (ACL) injury is one of the most common and disabling injuries in sports, significantly affecting knee stability and function. Physical therapy plays a crucial role in the recovery process, as well as preventing post-injury complications and recurrence. This study aims to conduct an integrative review of interventions that are potentially effective in the treatment of ACL injuries. This is an integrative review covering articles published between 2018 and 2024 in the Virtual Health Library (BVS) and Scientific Electronic Library Online (SciELO) databases. The results indicate that rehabilitation programs that combine muscle strengthening exercises, proprioceptive training, and joint mobilization techniques have better functional outcomes. Early and progressive interventions have been shown to be effective in reducing pain, improving joint stability, and accelerating return to activities. In addition, the inclusion of neuromuscular training and individualized protocols contributed to lower rates of re-injury. It is concluded that physical therapy is important in the postoperative care of ACL cases, contributing to the recovery and, consequently, the improvement of these patients’ quality of life. After all, rehabilitation work aims to restore joint stability, increase range of motion and muscle potential, and with these aspects combined, it is likely that the patient will return to their daily activities.